ANALISIS KAUSALITAS ANTARA TABUNGAN MASYARAKAT DENGAN PERTUMBUHAN EKONOMI DI KOTA PALEMBANG (TAHUN 1995-2013) - Mardalena Mardalena; Suhel Suhel (Department of Development Economics, Universitas Sriwijaya, 2015)
The goal of this research is to analyze the pattern of the relationship between private savings and economic growth in Palembang period 1995-2013. To determine the relationship pattern used Granger causality test. There are four possibilities causal relationship between St (public savings) and Yt (economic growth) will appear on the causality test: (1). Causality one direction is Yt (economic growth) effect or causes St. (public savings), (2). Causality one direction ie St (public savings) affect or cause Yt (economic growth), (3). Yt (economic growth) and St (public savings) are independent of each other, and (4). Yt (economic growth) and St (public savings) are dependent on each other. Granger causality test results indicate that the economic growth of the previous year affecting people's savings in Palembang. Savings communities affected by the economic growth of 97% and 3% are influenced by other factors. Each 1% increase in economic growth will increase public savings in Palembang is 86%. Future studies are expected to incorporate other factors that affect people's savings and economic growth as the variable interest rates of savings and investment in the city of Palembang. Keywords: Economic Growth, Savings Society, causality